HepCare Europe: a service innovation project. HepCheck: enhancing HCV identification and linkage to care for vulnerable populations through intensified outreach screening. A prospective multisite feasibility study. (29th November 2019) - Barror, Suzanne; Avramovic, Gordana; Oprea, Cristiana; Surey, Julian; Story, Alistair; Macías, Juan; Cullen, Walter; Crowley, Des; Horan, Aidan; Naughton, Anna Marie; Iglesias, Maria; Ianache, Irina; et al.
Abstract: Objectives: Hepatitis C is one of the main causes of chronic liver diseases worldwide. One of the major barriers to effecting EU- and WHO-mandated HCV elimination by 2030 is underdiagnosis. Community-based screening strategies have been identified as important components of HCV models of care. HepCheck Europe is a large-scale intensified screening initiative aimed at enhancing identification of HCV infection among vulnerable populations and linkage to care. Methods: Research teams across four European countries were engaged in the study and rolled out screening to high-risk populations in community addiction, homeless and prison services. Screening was offered to 2822 individuals and included a self-administered questionnaire, HCV antibody and RNA testing, liver fibrosis assessment and referral to specialist services. Results: There was a 74% ( n =2079) uptake of screening. The majority (85.8%, n =1783) were male. In total 44.6% ( n =927) of the sample reported ever injecting drugs, 38.4% ( n =799) reported ever being homeless and 27.9% ( n =581) were prisoners. In total 397 (19%) active HCV infections were identified and 136 (7% of total sample and 34% of identified active infections) were new cases. Of those identified with active HCV infection, 80% were linked to care, which included liver fibrosis assessment and referral to specialist services. Conclusions: HepCheck's screening and linkage to care is a clear strategy for reaching high-risk populations, including those at highest risk of transmission who are not accessing any type of care in the community. Elimination of HCV in the EU will only be achieved by such innovative, patient-centred approaches.